Multikinase inhibitors modulate non-constitutive proteasome expression in colorectal cancer cells - Burov, Alexander; Grigorieva, Ekaterina; Lebedev, Timofey; Vedernikova, Valeria; Popenko, Vladimir; Astakhova, Tatiana; Leonova, Olga; Spirin, Pavel; Prassolov, Vladimir; Karpov, Vadim; Morozov, Alexey (Frontiers in Molecular Biosciences, 2024)
Proteasomes are multi-subunit protein complexes responsible for degradation of most intracellular proteins to peptides. Immunoproteasomes and intermediate proteasomes (together non-constitutive proteasomes) are specific forms of proteasomes frequently associated with immune response, antigen presentation, inflammation and stress. Expression of non-constitutive proteasome subunits has a prognostic value in several types of cancer. Thus, factors that modulate non-constitutive proteasome expression in tumors are of particular interest. Multikinase inhibitors (MKI) demonstrate promising results in treatment of different solid cancers. At the same time, their immunomodulatory properties and, specifically, effects on non-constitutive proteasome expression in cancer cells are poorly investigated. Here we show that expression of non-constitutive proteasomes is increased in BRAFmutant colorectal tumors and that non-constitutive proteasomes are upregulated by BRAF/MEK inhibition. We demonstrated that multikinase inhibitors regorafenib and sorafenib stimulate activity and synthesis of non-constitutive proteasomes in two colorectal cancer cell lines, engineered to express fluorescent non-constitutive proteasomes. Moreover, MKIs induced oxidative stress and redistribution of proteasomes within cells: sorafenib stimulated formation of cytoplasmic aggregates, containing proteolyticaly active non-constitutive proteasomes, while regorafenib had no such effect. Obtained results indicate that MKIs might affect the crosstalk between cancer cells and immune cells, via modulation of intracellular proteasome pool.